NEW UYTENBOGAARDTITE FIND IN THE USSR - Bradinskaya Ye.M.; Ushchapovskaya Z.F.; Barankevich V.G.; Fomina V.A. (My University, 1990)
The silver-gold sulfide investigated by the authors, uytenbogaardtite, was discovered in part of a gold-bearing quartz vein in the oxidation zone of one gold-silver deposit in western Uzbekistan, where the primary ore is confined to carbonaceous carbonate shale with siltstone and sandstone partings of Middle Carboniferous age. Gold in the vein quartz sample is closely intergrown with black crusts and clusters of compact or friable, secondary material no larger than 1 to 2 mm. They contain relict grains of acanthite and uytenbogaardtite, ranging in size from 0.01 to 0.6 × 1.2 mm, and are colloform mixtures of finely divided or amorphous secondary minerals, which also include well-crystallized supergene covellite, aalachite, chalcocite and cerargyrite. In the vein quartz there are grains of slightly oxidized hypogene arsenopyrite, pyrite and pyrrhotite as well.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная